Biased Beliefs and Entry into Scientific Careers - Ina Ganguli; Patrick Gaule; Danijela Vuletić Čugalj (Institute of Labor Economics (IZA), 2020)
We investigate whether excessively optimistic beliefs may play a role in the persistent demand for doctoral and post-doctoral training in science. We elicit the beliefs and career preferences of doctoral students through a novel survey and randomize the provision of structured information on the true state of the academic market and information through role models on non-academic careers. One year later, both treatments lead students to update their beliefs about the academic market and impact career preferences. However, we do not find an effect on actual career outcomes 2 years post-intervention.
Keywords: I23; D80; D84; J24; 330; career preferences; biased beliefs; information; higher education; science